2003
DOI: 10.1002/anie.200390035
|View full text |Cite
|
Sign up to set email alerts
|

Novel T‐Shaped 14‐Electron Platinum(II) Complexes Stabilized by One Agostic Interaction

Abstract: The stereoelectronic properties of the PR2(2,6‐Me2C6H3) (R=Ph, Cy) ligand can be used to stabilize an unprecedented class of 14‐electron platinum(II) complexes. The X‐ray analysis of the cyclometalated cyclohexyl derivative reveals an agostic interaction between the Pt center and an o‐methyl moiety (see picture). The fast and reversible formation of three‐coordinate platinum–hydrido complexes occurs by reaction with H2, and is achieved through the cleavage of a platinum–carbon bond.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
22
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(29 citation statements)
references
References 40 publications
7
22
0
Order By: Relevance
“…[17] Similar agostic coordinations have been found for related isoelectronic complexes of Ni II , [19] Pt II , [20][21][22] and Rh I . [23,24] Strictly speaking, counting the agostic coordination, these complexes are tetracoordinated.…”
Section: Introductionmentioning
confidence: 67%
“…[17] Similar agostic coordinations have been found for related isoelectronic complexes of Ni II , [19] Pt II , [20][21][22] and Rh I . [23,24] Strictly speaking, counting the agostic coordination, these complexes are tetracoordinated.…”
Section: Introductionmentioning
confidence: 67%
“…Previous mechanistic studies on platinum complexes bearing phosphine or pyridine ligands have suggested that cis-trans isomerization either proceeds by a dissociative mechanism that involves loss of the phosphine, pyridine, or halide ligands leading to a three-coordinate T-shaped complex intermediate, or by an associative mechanism that involves coordination of the phosphine or pyridine ligand leading to a five-coordinate intermediate. [45] We found that the conversion of complex 5 a to 5 b proceeded efficiently when 5 a was heated in [D 8 ]toluene at 200 8C for 2 days in a J. Young NMR tube to give an isolated yield of 73 %.…”
Section: Mechanistic Investigationsmentioning
confidence: 84%
“…In [Ni( [14]ane-S 4 )]BF 4 (TTCDNI, Table 1) [36] and the perchlorate of a related macrocyclic complex (MAXSOT, Table 1), [37] moderate deviations from the octahedral shape result from relatively small differences between the bonded NiÀS distances (2.18 ) and the nonbonded contacts between the Ni atom and the BF 4…”
Section: Resultsmentioning
confidence: 98%
“…[9] The appreciation of the role that such secondary interactions may have led a group of researchers to say that a family of dithiolene copper complexes is "blessed with secondary coordination ability." [8] Other ways of referring to imprecise coordination numbers in transition-metal chemistry include the naming of some copper(I) complexes as "quasi-two-coordinate" to allude to the weak bonding of additional ligands, [10] or the use of the expression "semi-coordinating interaction," [11] not to mention the widely recognized "agostic interactions" or secondary coordination of ancillary groups [12] that may help, for example, stabilize low coordination numbers [13] or less common coordination geometries, such as a T-shaped tricoordination [14] or a seesaw tetracoordination. [15] Among the variety of examples that can be found in the literature, we choose to mention in more detail here only some illustrative ones.…”
Section: Introductionmentioning
confidence: 99%